Association of Clinical Features and Hematological Laboratories between Ph (+)/BCR-ABL (+) Chronic Myeloid Leukemia and Other Type of Ph/BCR-ABL Chronic Myeloid Leukemia - Wulyo Rajabto; A. Harryanto; Hilman Tadjoedin; Kuntjoro Harimurti (Jurnal Penyakit Dalam Indonesia)
Introduction. Patients with chronic phase Chronic Myeloid Leukemia (CML) at Hematology-Medical Oncology Clinic Department of Internal Medicine dr. Cipto Mangunkusumo National Hospital who haveperformed cytogenetic and RTPCR BCR-ABL examination showed: Ph (+)/BCR-ABL (+) CML and other type of Ph/BCR-ABL CML. This study aims to identify the clinical features and hematological laboratories of chronic phase CML, the proportion of Ph (+)/BCR-ABL (+) CML, and association of clinical features and hematological laboratories between Ph (+)/BCR-ABL (+) CML and other type of Ph/BCR-ABL CML.